Merbabu Art Fest sebagai Ruang Konstruksi Sosial: Kesenjangan Internalisasi Nilai - Satrio Katon Prayogi; Antik Tri Susanti; Arianti Ina Restiani Hunga (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Purwogondo hamlet in Boyolali Regency has long been associated with a negative social stigma involving alcohol consumption, brawls, and gambling among its youth. Merbabu Art Fest (MAF) was established in 2018 as a collective community response to transform this image through arts and culture. This study analyses the social construction of MAF as a space for the social construction of the Purwogondo community, drawing on Peter L Berger and Thomas Luckmann’s theory of social construction of reality. A qualitative case-study approach was employed through in-depth interviews, participant observation, and document analysis involving the festival’s founders, foundation managers, government officials, cultural partners, and neutral residents. The findings show that MAF was formed through three interrelated dialectical moments: the externalization of collective anxiety over the negative stigma, the objectivation of MAF into a culturally and politically recognized institution marked by an interfaith prayer tradition, and the internalization of awareness and collective pride as ‘wong ndeso’ (villagers) among both youth and older residents. Nevertheless, this internalization remains uneven among audiences outside the core organizing structure, as reflected in persistent problems of alcohol consumption and post-event waste. These findings affirm that the success of cultural transformation through community festivals strongly depends on an actor’s structural proximity to the institution’s center of meaning production.